Socio-Technical Governance of Smart Grids: Integrating Electrical Engineering Innovation with Public Administration Reform - Corinne Zylstra (Universitas Muhammadiyah Jakarta, 2026)
Smart grids are increasingly promoted as a strategic response to the challenges of energy reliability, urban resilience, renewable energy integration, and digital public service transformation. However, most discussions of smart grids remain dominated by technical concerns, including automation, advanced metering infrastructure, artificial intelligence, distributed energy resources, communication protocols, and grid stability. While these engineering dimensions are essential, they are insufficient to explain whether smart grids can generate sustainable public value. Smart grids are not merely electrical systems equipped with digital technologies; they are socio-technical public systems that involve institutions, regulations, citizens, private vendors, data governance, accountability mechanisms, and public administration capacity. This article develops a socio-technical governance framework for integrating electrical engineering innovation with public administration reform. Using an integrative literature and policy synthesis, the article examines the relationship between smart grid technology, digital government, institutional coordination, responsible artificial intelligence, data protection, and citizen-centred public service delivery. The results identify four interrelated governance dimensions: technical infrastructure governance, institutional and regulatory governance, data and algorithmic governance, and citizen-centred public value governance. The discussion argues that smart grid implementation requires a shift from technology deployment to governance transformation. Governments and utilities must develop interoperability standards, transparent procurement systems, privacy safeguards, algorithmic accountability, inter-agency coordination, participatory mechanisms, and public value indicators. The article concludes that smart grid innovation can strengthen public administration reform when technical excellence is embedded in accountable, inclusive, adaptive, and citizen-centred governance arrangements.